Citrullus colocynthis an Important Plant in Indian Traditional System of Medicine - Kapoor, Manish; Kaur, Navneet; Sharma, Chanchal; Kaur, Gurdeep; Kaur, Rupinder; Batra, Kajal; Rani, Jyoti (Pharmacognosy Reviews)
Citrullus colocynthis (L.) Schrad, commonly known as Colocynth, a member of Cucurbitaceae is native to Mediterranean region and Asia. It is a wild, perennial, herbaceous, non-tough, harsh, angular vine with lobular tendrils, alternate leaves and small yellow monoecious flowers. Recently, various researches have been done to assess restorative capability of the plant. It contains various phytochemical constituents such as alkaloids, carbohydrates, flavonoids, tannins, triterpenoids, proteins, saponins and steroids along many pharmacological properties viz. diuretic, hypolipidemic, anti-cancerous, antioxidant, anti-microbial. This work is an endeavor to assemble and explore the various phytochemical and pharmacological properties announced till date.
Keywords: Citrullus colocynthis; Colocynth; Cucurbitacins; Pharmacological activities; Vine of Sodom